2022
DOI: 10.1039/d1nj05621b
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, characterization,in vitroscreening, molecular docking, 3D-QSAR, and ADME-Tox investigations of novel pyrazole derivatives as antimicrobial agents

Abstract: In this work, we report the synthesis of some new pyrazole derivatives via an efficient and practical procedure. The structures of the obtained compounds were established using different spectroscopic techniques...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…After selecting the ideal N and Q 2 for the 3D-QSAR modeling design, we evaluate the overall significance of the developed model by computing statistical parameters such as the coefficient of determination ( R 2 ), the standard error of estimates (SEE), and F -value (Fischer’s test). If the values of R 2 > 0.6 and F test > 0.3 and low SEE, the model 3D-QSAR will be able to provide an ideal description of pIC 50 values based on the structural properties of investigated molecules [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…After selecting the ideal N and Q 2 for the 3D-QSAR modeling design, we evaluate the overall significance of the developed model by computing statistical parameters such as the coefficient of determination ( R 2 ), the standard error of estimates (SEE), and F -value (Fischer’s test). If the values of R 2 > 0.6 and F test > 0.3 and low SEE, the model 3D-QSAR will be able to provide an ideal description of pIC 50 values based on the structural properties of investigated molecules [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…The presence of heterocyclic compounds as the main structural motif in a variety of biologically active, natural and synthetic molecules has led to the development of new methodologies of their synthesis. In this context, we have been interested in the synthesis of various aza-heterocyclic derivatives with potential biological activities, using easy and reproducible synthesis strategies [32][33][34][35]. In the present work, we describe the synthesis of quinazolin-4(3H)-one-isoxazoline hybrids according to the pathway shown in Scheme 1.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…The synthesis of new heterocycle molecules based on the hybridization of quinazolinone and isoxazoline pharmacophores is a promising avenue in modern medicinal chemistry [31]. In this regard and in continuation of our ongoing research focused on the design of new bioactive compounds [32][33][34][35], we reported in this work, the synthesis and characterization of new quinazolinone-isoxazoline hybrids. The synthesis of the target compounds 4a-h was performed using 1,3-dipolar cycloaddition reaction between arylnitriloxides 3a-h and Nallylquinazolinone 2.…”
Section: Introductionmentioning
confidence: 98%
“…In continuation of our previous efforts in the development of new aza-heterocyclic antimicrobial candidates, we report in the present work the synthesis, structural identification, and biological activity assessment of new poly heterocyclic molecules incorporating both pyrazole and isoxazoline cores. The synthesis of these heterocycles is carried out from aza-aurones by N-alkylation and 1,3-dipolar cycloaddition reactions.…”
Section: Introductionmentioning
confidence: 98%